2019
DOI: 10.1039/c8qo01421c
|View full text |Cite
|
Sign up to set email alerts
|

Additive-free regio- and diastereoselective construction of fully-substituted isoxazolidines employing diazo compounds

Abstract: An efficient additive-free three-component access to densely functionalized isoxazolidines using diazo compounds, nitrosoarene, and allenic esters has been uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…To address this limitation, our group reported the additive-free three-component synthesis of phosphonylated isoxazolidines 35 via the [3 + 2] cycloaddition reaction between allenoates 34 and nitrone generated in situ from Seyferth-Gilbert reagent 1 and nitrosoarenes 33. [35] A brief optimization of the reaction conditions revealed that nitrosobenzene reacts with Seyferth-Gilbert reagent and γmethyl allenoate in CH 3 CN at 50°C to furnish the phosphonylated isoxazolidine in the highest yield. Under the optimized reaction conditions, we set to examine the substrate scope for the protocol (Scheme 22).…”
Section: Synthesis Of Isoxazolidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this limitation, our group reported the additive-free three-component synthesis of phosphonylated isoxazolidines 35 via the [3 + 2] cycloaddition reaction between allenoates 34 and nitrone generated in situ from Seyferth-Gilbert reagent 1 and nitrosoarenes 33. [35] A brief optimization of the reaction conditions revealed that nitrosobenzene reacts with Seyferth-Gilbert reagent and γmethyl allenoate in CH 3 CN at 50°C to furnish the phosphonylated isoxazolidine in the highest yield. Under the optimized reaction conditions, we set to examine the substrate scope for the protocol (Scheme 22).…”
Section: Synthesis Of Isoxazolidinesmentioning
confidence: 99%
“…However, the formation of nitrones was limited, owing to the need for an additional step for its preparation. To address this limitation, our group reported the additive‐free three‐component synthesis of phosphonylated isoxazolidines 35 via the [3+2] cycloaddition reaction between allenoates 34 and nitrone generated in situ from Seyferth‐Gilbert reagent 1 and nitrosoarenes 33 [35] …”
Section: Synthesis Of Isoxazolidinesmentioning
confidence: 99%
“…The scope of trifluoromethylnitrone 51 was subsequently explored in [3 + 2]‐cycloaddition with allenic esters 6 in 2019 (Scheme 28) [50]. This three‐component protocol afforded trifluoromethylated isoxazolidines 58 in high yields.…”
Section: Application Of Trifluorodiazoethane In Cf3‐heterocyclesmentioning
confidence: 99%
“…In 2018, our group developed an effective and general three-component reaction to synthesize trifluoromethylated spiro-isoxazolidine-oxindoles 56 (Scheme 27) [49]. The method utilized a [3 + 2]cycloaddition reaction of phenacylideneoxindoles 55 with trifluoromethylnitrone 51, generated in situ from The scope of trifluoromethylnitrone 51 was subsequently explored in [3 + 2]-cycloaddition with allenic esters 6 in 2019 (Scheme 28) [50]. This three-component protocol afforded trifluoromethylated isoxazolidines 58 in high yields.…”
Section: Synthesis Of Cf 3 -Substituted Isoxazolidines Oxazolines Iso...mentioning
confidence: 99%
“…Alternatively, diazo compounds undergoing the noncarbenoid-type intermediate process can also been used for three-component reaction. For example, three-component reactions involving diazo compounds and nirosoarenes are well developed, in which nitrone intermediates would be formed initially with diazo compounds used as noncarbenoid-type nucleophiles, and participate in 1,3-dipolar cycloaddition with alkenes or alkynes to produce isoxazolidines or aziridines, respectively. However, the related asymmetric example is rare.…”
mentioning
confidence: 99%